SRI36160 is a specific inhibitor of Wnt/β-catenin signaling in human pancreatic and colorectal cancer cells. (28th March 2017) - Li, Yonghe; Oliver, Patsy G.; Lu, Wenyan; Pathak, Vibha; Sridharan, Sivaram; Augelli-Szafran, Corinne E.; Buchsbaum, Donald J.; Suto, Mark J.
Abstract: Activation of Wnt/β-catenin signaling is associated with pancreatic and colorectal cancer, among others. To-date, there are no FDA-approved small molecule Wnt/β-catenin inhibitors and many past efforts resulted in compounds with undesirable off-target effects. We recently identified a series of benzimidazole analogs as potent inhibitors of Wnt/β-catenin signaling. Here, we show that the lead compound SRI36160 displayed selective Wnt inhibition and potent antiproliferative activity in pancreatic and colorectal cancer cells. Moreover, SRI36160 had no effect on STAT3 and mTORC1 signaling in pancreatic and colorectal cancer cells, and was not effective in inhibiting proliferation of non-cancerous cells. Our findings suggest that this series of benzimidazole analogs presents a novel approach for the treatment of Wnt-dependent cancers such as colorectal and pancreatic cancer. Highlights: SRI36160 is a novel potent inhibitor of Wn/β-catenin signaling in cancer cells. SRI36160 displays potent activity against cancer cell proliferation. SRI36160 induces cancer cell apoptosis. SRI36160 has no effect on STAT3 and mTORC1 signaling in cancer cells. SRI36160 is not effective in inhibiting proliferation of non-cancerous cells.